TRANSLANGUAGING PRACTICE IN EFOC CLASS: STUDENTS’ PERCEPTION - Handayani, Magpika (Jurnal Ilmiah Spectral, 2025)
This research aims to explore management students' perceptions of translanguaging practices in the EFOC class within the management study program. Using qualitative research in the form of case study, the writer investigated the perception of students on translanguaging practice.  The data was obtained from the respondents’ response related to the translanguaging practice in EFOC class in understanding the instruction. An interview was conducted with the representative to clarify their perception related to translanguaging practice they have experienced in EFOC class. The data were reread to understand the situation and aligned it with the classroom situation. The result shows that Many students have limited exposure to English due to their educational and social backgrounds, having primarily learned the language in school with infrequent practice, while their community language prevails. However, students believe that the translanguaging practice has facilitated their understanding and enhanced their interactions with peers. They did not view translanguaging as a disrespectful or confusing strategy in the EFOC class. Conversely, they strongly agree that this practice has been beneficial in comprehending the lecturer's instructions and is vital for the EFOC class.